Secure Base Scripts are Associated with Maternal Parenting Behavior across Contexts and Reflective Functioning among Trauma-Exposed Mothers - Huth-Bocks, Alissa C. (Attach Hum Dev, 2014)
There is growing evidence that ‘secure-base scripts’ (Waters & Waters, 2006) are an important part of the cognitive underpinnings of internal working models of attachment. Recent research in middle class samples has shown that secure-base scripts are linked to maternal attachment-oriented behavior and child outcomes. However, little is known about the correlates of secure base scripts in higher-risk samples. Participants in the current study included 115 mothers who were oversampled for childhood maltreatment and their infants. Results revealed that a higher level of secure base scriptedness was significantly related to more positive and less negative maternal parenting in both unstructured free play and structured teaching contexts, and to higher reflective functioning scores on the Parent Development Interview-Revised Short Form (Slade, Aber, Berger, Bresgi, & Kaplan, 2003). Associations with parent-child secure base scripts, specifically, indicate some level of relationship-specificity in attachment scripts. Many, but not all, significant associations remained after controlling for family income and maternal age. Findings suggest that assessing secure base scripts among mothers known to be at risk for parenting difficulties may be important for interventions aimed at altering problematic parental representations and caregiving behavior.